2020
DOI: 10.1021/acsaem.0c00633
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Coated Porous Titanium Niobium Oxides as Anode Materials of Lithium-Ion Batteries for Extreme Fast Charge Applications

Abstract: The development of electric vehicles (EVs) has been restricted by severe lithium plating in lithium-ion batteries (LIBs) with graphite as the anode. To mitigate the lithium plating issue, carbon coated porous titanium niobium oxides (TNO@C) have been synthesized and evaluated as anode materials for extreme fast charge (XFC) applications in LIBs. Various methods have been utilized to optimize the full cells with LiNi0.6Mn0.2Co0.2O2 (NMC) as the cathode and TNO@C as the anode, delivering a high energy density of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 66 publications
1
30
0
Order By: Relevance
“…Moreover, some studies have shown that the introduction of Na into LMROs can relieve the voltage drop during cycling, while the K‐doped cathode can exhibit a capacity of 244 mAh g −1 at 0.5C after 100 cycles and even 133 mAh g −1 at 10C. [ 211 ] In addition to the above‐mentioned metal ions, anions are also possible dopants, among which F is the most attractive element because it exhibits a two‐fold increase in the ionic conductivity of modified LMROs while improving the structural stability, especially at high temperature; moreover, the use of F provides good voltage retention of up to ≈96% at 0.5C after 200 cycles. [ 212 ] It has been also reported that F ‐ can prevent the compound from undergoing too much oxygen redox, which can trigger oxygen loss.…”
Section: Promising Candidates Of Cobalt‐free Lithium‐ion Cathodesmentioning
confidence: 99%
“…Moreover, some studies have shown that the introduction of Na into LMROs can relieve the voltage drop during cycling, while the K‐doped cathode can exhibit a capacity of 244 mAh g −1 at 0.5C after 100 cycles and even 133 mAh g −1 at 10C. [ 211 ] In addition to the above‐mentioned metal ions, anions are also possible dopants, among which F is the most attractive element because it exhibits a two‐fold increase in the ionic conductivity of modified LMROs while improving the structural stability, especially at high temperature; moreover, the use of F provides good voltage retention of up to ≈96% at 0.5C after 200 cycles. [ 212 ] It has been also reported that F ‐ can prevent the compound from undergoing too much oxygen redox, which can trigger oxygen loss.…”
Section: Promising Candidates Of Cobalt‐free Lithium‐ion Cathodesmentioning
confidence: 99%
“…Apart from the aforementioned advantages, the working potential of Ti 2 Nb 2x O 4þ5x within 1.0 and 2.0 V, higher than the decomposition potential of common electrolyte (<0.8 V) and dendrite growth potential (<0.2 V), shows good security. [50] For another, Ti 2 Nb 2x O 4þ5x has shear ReO 3 -type crystal structure, which consists of a few tetrahedrons (0-4%) and octahedrons with shared angles and/or edges-greatly stabilizing the crystal structure during the energy storage process. Since 1950, the Ti-Nb-O system has been studied.…”
Section: Niobium-based Multielement Oxidementioning
confidence: 99%
“…TNO@MS HRs show excellent rate performance and cycling stability by establishing a good ionic and electronic conducting network through the interwoven structure, which provides a new idea for developing low-cost and high-capacity fast charging electrodes (Figure 10c). In addition, various carbon materials, [180,[183][184][185][186][187] metals [188][189][190] and metal oxides [191] can also be used to build multiphase systems together with niobiumbased oxides and demonstrate good fast charging performance.…”
Section: (13 Of 35)mentioning
confidence: 99%